A report from the AAPM Subcommittee on Guidelines for Competency Evaluation for Clinical Medical Physicists in Radiation Oncology. (8th July 2016) - Pavord, Daniel C.; Birnbaum, Steven; Boccuzzi, Douglas; deBoer, Steven; Freedman, D. Jay; Schell, Michael; Sutlief, Steven
Abstract : The goal of this report is to provide a framework from which an institution can develop a competency and credentialing program. It is not intended to be adopted as written, but rather as a list of suggestions from which the institution develops their program. A clear distinction should be made between the initial evaluation of the competency of new staff (credentialing) and the ongoing verification of the competency of existing staff. Furthermore, whenever new technologies are implemented, the entire staff would be subject to the credentialing process. Competencies involve the ongoing verification of the performance of a procedure according to the established policies and procedures at a facility. This can be done by audits of work product, direct observation of performance, self‐evaluation, or testing. PACS number(s): 87.10.‐e, 87.90.+y